Impact of Trade vs. Non-trade Policies on the Incidence of Child Labour: A Two-sector General Equilibrium Framework. (November 2016) - Chatterjee, Biswajit; Ray, Runa
The use of child labour has been widespread across developing nations. Although the incidence of child labour use has declined in recent years in the aggregate, its use has remained been quite widespread in different developing nations. Various policy interventions have been suggested and debated in international bodies to combat or reduce the incidence of child labour use in different activities in poor labour abundant countries. The present article develops a general equilibrium framework consisting of two sectors and three factors of production to investigate the efficacy of trade and non-trade policies on the incidence of child labour use and finds that although trade policy is ineffective in eradicating child labour, the use of non-trade policy is quite effective in this context.